Mature outcomes and prognostic indices in diffuse large B‐cell lymphoma in Malawi: a prospective cohort. (18th November 2018) - Painschab, Matthew S.; Kasonkanji, Edwards; Zuze, Takondwa; Kaimila, Bongani; Tomoka, Tamiwe; Nyasosela, Richard; Nyirenda, Ruth; Dhungel, Bal M.; Mulenga, Maurice; Chikasema, Maria; Tewete, Blessings; Mtangwanika, Asekanadziwa; et al.
Summary: Outcomes for diffuse large B‐cell lymphoma (DLBCL) in sub‐Saharan Africa (SSA) are poorly described. We report mature data from one of the first prospective SSA cohorts. Patients aged ≥18 years with DLBCL were enrolled in Malawi 2013–2017. Participants were treated with CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy and concurrent antiretroviral therapy (ART) if positive for human immunodeficiency virus (HIV+). Eighty‐six participants (mean age 47 years, standard deviation 13) were enrolled: 54 (63%) were male and 51 (59%) were HIV+, of whom 34 (67%) were on ART at DLBCL diagnosis. Median CD4 count was 0·113 cells × 10 9 /l (interquartile range [IQR] 0·062–0·227) and 25 (49%) had HIV viral load <400 copies/μl. Participants received median six cycles CHOP (IQR 4–6). No patients were lost to follow‐up and the 2‐year overall survival was 38% (95% confidence interval 28–49). In multivariable analyses, Eastern Cooperative Oncology Group performance status (PS) ≥2 and lactate dehydrogenase (LDH) >2× upper limit of normal (ULN) were associated with mortality. HIV status was not associated with mortality. A simplified prognostic model of LDH >2× ULN and PS ≥2 performed at least as well as the age‐adjusted International Prognostic Index. DLBCL can be successfully treated in SSA and outcomes did not differ by HIV status. A simplified prognostic model prognosticates well and may be easier to use in resource‐limited settings but requires validation.